The Concept of Human Rights from The Qur'an Perspective - Nurzannah Damyanti; Sabila Aida Nurazizah; Ryan Abdurrahman Fitriansyah; Asep Abdul Muhyi (Bulletin of Islamic Research, 2024)
This article focuses on the discussion of human rights in the Qur’an. The issue of human rights (HAM)   which is considered to have differences that are contrary to Islam is very problematic so it is interesting to discuss. Is it true that Islam does not recognize the concept of human rights? So how does the Koran as the main source of the Islamic religion discuss the concept of human rights? Therefore, this research aims to reveal the concept of human rights in the Al-Qur'an as the main source of Islam itself. This research uses a qualitative approach with descriptive-analytical methods, especially Maudhu'i's interpretation of verses relating to human rights. The results of this research found that the concept of human rights in Islam has existed since humans were born, as evidenced by the existence of verses in the Qur'an which are very relevant to the concept of human rights, including the rights to equality and justice contained in (QS.an Nisa: 58) the right to life (QS. al-Isra': 33) and the right to education (QS. At-Taubah: 122) with the interpretation related to this verse means that Islam is very relevant to the concept of human rights.